Ionic composition of ground waters and their distribution in Karnal District (Haryana) - Sharma, R C (Annals of Arid Zone, 2016)
222 ground water samples were collected from 108 villages in Kamal district (including the new Kurukshetra district) for water quality evaluation. Water samples were analysed for important chemical constituents. These waters were Na +-Mg +++-Ca++-K+ type with respect to cations. The anionic composition was HCO3--CO,---Cl-- SO4 -- type in waters of low EC and ClÂ -Â SO4--- HCO3 --C04 -- type in waters of high EC ranges. While mapping the quality of ground waters it was found that high salinity of water is a problem only in a part of Kaithal tehsil. In nearly all other parts of the district the ground waters have relatively low salt content. Poor quality of waters in majority of the cases could be ascribed to high contents of RSC. The occurrence of high RSC waters was more common in Kaithal than in any other tehsils , where average RSC in water was 4.9 me/I.